2003
DOI: 10.1109/jqe.2002.806189
|View full text |Cite
|
Sign up to set email alerts
|

Quadratic solitons: recent developments

Abstract: Multicolor optical solitons mediated by quadratic nonlinearities have been observed experimentally during the last few years in a variety of materials and geometries in a number of laboratories around the world. Today, many of the basic properties of the corresponding soliton families are theoretically well established. Nevertheless, experiments continuously reveal new surprises, and the topic is entering new theoretical and experimental territories. In this paper, we briefly outline the key features of the qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 77 publications
(64 reference statements)
0
17
0
Order By: Relevance
“…A comprehensive review on optical quadratic solitons was published by Buryak, Di Trapani, Skryabin, and Trillo [2002], and can be also found in a recent book by Kivshar and Agrawal [2003]. A number of overview papers on the theory and experimental generation of spatial parametric optical solitons in quadratic nonlinear media were published during the last years (Stegeman, Schiek, and Fuerst [1997]; Kivshar [1997]; Torner [1998]; Etrich, Lederer, Malomed, Peschel, and Peschel [2000]; Stegeman [2001]; Sukhorukov [2001]; Torruellas, Kivshar, and Stegeman [2001]), and summaries of the advances in the field were reported by ; Stegeman [1999]; Torner and Stegeman [2001]; Torner and Sukhorukov [2002]; Torner and Barthelemy [2003].…”
Section: Partially Coherent Vorticesmentioning
confidence: 99%
“…A comprehensive review on optical quadratic solitons was published by Buryak, Di Trapani, Skryabin, and Trillo [2002], and can be also found in a recent book by Kivshar and Agrawal [2003]. A number of overview papers on the theory and experimental generation of spatial parametric optical solitons in quadratic nonlinear media were published during the last years (Stegeman, Schiek, and Fuerst [1997]; Kivshar [1997]; Torner [1998]; Etrich, Lederer, Malomed, Peschel, and Peschel [2000]; Stegeman [2001]; Sukhorukov [2001]; Torruellas, Kivshar, and Stegeman [2001]), and summaries of the advances in the field were reported by ; Stegeman [1999]; Torner and Stegeman [2001]; Torner and Sukhorukov [2002]; Torner and Barthelemy [2003].…”
Section: Partially Coherent Vorticesmentioning
confidence: 99%
“…1,2 During the last decade, quadratic solitons have been experimentally observed in a variety of materials, mostly in the spatial domain. 3 More recently, several experiments on temporal soliton and solitonlike pulse shaping have also been reported. 4 -8 By using the pulse tilting technique, Trapani et al 5 observed temporal solitons in BaB 2 O 4 ͑BBO͒ and Liu et al 6 observed spatiotemporal solitons in LiIO 3 .…”
mentioning
confidence: 99%
“…Corresponding solution of main system (12) and (13) In this case, we obtain the following similarity variables:…”
Section: Lie Symmetry Analysismentioning
confidence: 99%
“…Optical solitons is one of the most active areas of research in the field of nonlinear optics [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. It is evident, from a variety of reported results, that the main focus is on integrability issue in fiber optics, photonic crystal, metamaterials and metasurfaces.…”
Section: Introductionmentioning
confidence: 99%